Helicobacter pylori infection affects the human gastric microbiome, as revealed by metagenomic sequencing. Issue 6 (25th March 2022) - Wang, Daoming; Zhang, Tongda; Lu, Yueqi; Wang, Changzheng; Wu, Yumei; Li, Jiandong; Tao, Ye; Deng, Le; Zhang, Xiaoyin; Ma, Jinmin
Abstract : Helicobacter pylori infection is a prevalent infectious disease, associated with many gastric diseases, including gastritis, gastric ulcer, and gastric cancer. To reveal the characteristics of the gastric microbiome in patients infected with H. pylori, we performed metagenomic shotgun sequencing of stomach swab samples from 96 patients and then conducted metagenomic association analyses between alterations in the gastric microbiome and H. pylori infection status. The overall composition of the gastric microbiota in H. pylori‐infected individuals was distinctly different from the negative controls; H. pylori became the dominant species after colonizing the human stomach and significantly decreased the α‐diversity of the gastric community ( P  < 0.05, Wilcoxon rank‐sum test). We also identified 6 HPI‐associated microbial species (FDR < 0.05, Wilcoxon rank‐sum test): Stenotrophomonas maltophilia, Stenotrophomonas unclassified, Chryseobacterium unclassified, Pedobacter unclassified, Variovorax unclassified, and Pseudomonas stutzeri . Furthermore, 55 gastric microbial pathways were enriched in the H. pylori ‐positive group, whereas only 2 pathways were more abundant in the H. pylori ‐negative group: dTDP‐L‐rhamnose biosynthesis and tetrapyrrole biosynthesis (FDR < 0.05, Wilcoxon rank‐sum test). Gastritis was not associated with non‐ H. pylori species in the stomach ( P  > 0.05, Wilcoxon rank‐sum test). This study revealed alterations in gastric microbial taxa and function associated with HPI in the Chinese population, which provides an insight into gastric microbial interactions and their potential role in the pathological process of gastric diseases. Abstract : Wang et al. performed shotgun metagenomic sequencing on gastric endoscopy samples from Chinese patients with gastric symptoms and then performed metagenomic analysis. The data suggest that Helicobacter pylori infection is associated with gastric microbial taxonomic and functional alterations, providing insights into gastric microbial interactions and their potential role in the pathological process of gastric diseases.